miR-204 suppresses cancer stemness and enhances osimertinib sensitivity in non-small cell lung cancer by targeting CD44 - Wu, Shang-Gin; Chang, Tzu-Hua; Tsai, Meng-Feng; Liu, Yi-Nan; Huang, Yen-Lin; Hsu, Chia-Lang; Jheng, Han-Nian; Shih, Jin-Yuan (Molecular therapy. Nucleic acids, 2024)
Osimertinib is an effective treatment option for patients with advanced non-small cell lung cancer (NSCLC) with EGFR activation or T790M resistance mutations; however, acquired resistance to osimertinib can still develop. This study explored novel miRNA–mRNA regulatory mechanisms that contribute to osimertinib resistance in lung cancer. We found that miR-204 expression in osimertinib-resistant lung cancer cells was markedly reduced compared to that in osimertinib-sensitive parental cells. miR-204 expression levels in cancer cells isolated from treatment-naive pleural effusions were significantly higher than those in cells with acquired resistance to osimertinib. miR-204 enhanced the sensitivity of lung cancer cells to osimertinib and suppressed spheroid formation, migration, and invasion of lung cancer cells. Increased miR-204 expression in osimertinib-resistant cells reversed resistance to osimertinib and enhanced osimertinib-induced apoptosis by upregulating BIM expression levels and activating caspases. Restoration of CD44 (the direct downstream target gene of miR-204) expression reversed the effects of miR-204 on osimertinib sensitivity, recovered cancer stem cell and mesenchymal markers, and suppressed E-cadherin expression. The study demonstrates that miR-204 reduced cancer stemness and epithelial-to-mesenchymal transition, thus overcoming osimertinib resistance in lung cancer by inhibiting the CD44 signaling pathway. [Display omitted] miR-204 reduced cancer stemness and the epithelial-to-mesenchymal transition, thus overcoming osimertinib resistance in lung cancer by inhibiting the CD44 signaling pathway. miR-204 may be a novel biomarker for predicting the treatment effectiveness of osimertinib in lung cancer treatment.